PENGARUH METODE DEMONSTRASI TERHADAP KETERAMPILAN MENULIS DESKRIPSI PADA SISWA KELAS IV SEKOLAH DASAR - Supiati Ningsih, Nani; Satrio Wibowo; Galuh Kartika Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The low level of writing skills in the four grade of SDN sambibuluh, Taman Subdistrict, Sidoarjo Regency is the background of this research. Description is one type of essay that students must master, especially in Indonesian language subject. However, there are still many students have minimum skill on it. This problem can be known from daily score, they have under minimum score in writing descriptions in Indonesian language subjects which is under 70. The purpose of this research is to determine the effect of the demonstration method on descriptive writing skills for Indonesian language learning in grade IV elementary school students and to determine student's responses after using the demonstration method on descriptive writing skills. This research is quantitative research using Pre-Experiment method with One Short Case Study Design. This research was conducted in class IV of SDN Sambibuluh, Taman District, Sidoarjo Regency. The sample for this research was 25 experimental class students consisting of 10 male and 15 female. This research uses SPSS calculations to obtain results. Based on the results of statistical tests, it was found that the asymp sig (2-tailed) value was 0.003 < 0.05. According to the basis for decision making in the Wilcoxon test, this means that there is a significant difference between the pretest and posttest scores, so it can be concluded that there is a significant effect of using the demonstration method on the ability to write descriptions in grade IV elementary school students. Class IV students' responses to the use of the demonstration method received good criteria with a presentation of 80%.